How public participation could improve public decisions on rail investments? - Pagliara, Francesca; Di Ruocco, Irina (Regional science policy & practice)
Traditional cost/benefit analysis does not explicitly consider public participation in its computation. It neglects that stakeholders should be considered during the process of project evaluation. In this paper the costs and benefits of participatory activity are measured with the aim of analysing whether this economic measurement provides a way forward in project evaluation. Through the case study of the high speed rail line between Lyon and Turin, it is demonstrated that public participation should move forward as a field. Resumen. El análisis tradicional de costo/beneficio no considera explícitamente la participación pública en su cálculo. Ignora que las partes interesadas deben ser tenidas en cuenta durante el proceso de evaluación del proyecto. En este artículo se miden los costos y beneficios de la actividad participativa con el objetivo de analizar si este indicador económico proporciona una forma de mejorar la evaluación de proyectos. Mediante el estudio de caso de la línea de tren de alta velocidad entre Lyon y Turín, se demuestra que la participación pública debe avanzar como un área de estudio. 抄録: 伝統的な費用便益分析では、その計算において住民参加を明確には考慮に入れられていない。プロジェクトの評価においては、利害関係者を考慮に入れるべきであるが、それが看過されている。本稿では、この経済的測定により最善のプロジェクト評価が行われるかどうかを分析する目的で参加活動の費用と便益を測定する。ケーススタディとしてリヨンとトリノ間を結ぶ高速鉄道の検討から、住民参加はひとつの分野として推進するべきであることが示される。